Substratos vítreos ativos baseados em vidros borofosfato para o crescimento de nanopartículas de metais de transição - Lenz, Guilherme Felipe (2017)
This work proposes the synthesis and characterization of borophosphate glasses as active substrates for the growth of silver, copper and nickel-cobalt nanoparticles, and their respective oxides, with subsequent application for catalytic reduction of p-nitrophenol and catalytic oxidation of benzyl alcohol. In order to improve chemical resistance to moisture, borophosphate glasses, with molar composition NaH2 PO4/H3BO3 = 2, were doped adding between 0 and 30 mol% Al 3+ ions. As the Al 3+ concentration increased, the water absorption of glasses decreased. The samples doped with 25 and 30 mol% Al 3+, fused at 1050 °C, suffered crystallization, with AlPO4 triclinic phase precipitation, determinated by X ray diffraction (XRD). Besides water absorption profile and XRD, the matrix were characterized by infrared spectroscopy (FTIR) and Raman spectroscopy. The elementary composition was determined by Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES). The sample doped with 20 mol% Al 3+ was chosen for AgNO3, Cu2O and Ni2O3-Co2O3 doping. This glass composition enable the fusion at relative low temperatures (1050 °C) and allowed the metallic nanoparticles growth by bottom-up process, after the thermal treatment on hydrogen gas atmosphere: metallic silver (Ag-NPs), copper (Cu-NPs) and nickel-cobalt (NiCo-NPs) nanoparticles were formed. The thermal annealing of Ag-NPs and Cu-NPs under air atmosphere at 400 °C enables the synthesis of supported silver oxide nanoparticles (AgO-NPs) and copper oxide nanoparticles (CuO-NPs). The doped borophosphate glasses and their nanoparticles were characterized by UV-Vis spectrophotometry, FTIR and Raman spectroscopy, XRD, elementary composition by ICP-OES and scanning electron microscopy (SEM). Copper doped borophosphate glass pellets containing CuO-NPs and Cu-NPs were applied in the catalytic reduction of p-nitrophenol by NaBH4. Better result was obtained with CuO-NPs decorated glass pellets, what was attributed to in situ reduction of CuO to Cu0 and surface hydrogen transfer to p-nitroenolate. AgO-NPs, CuO-NPs and NiCo-NPs supported on borophosphate glasses were applied in the catalytic oxidation of benzyl alcohol (BnOH) using water or acetonitrile (ACN) as solvent and NaOCl as oxidant. The bests results were found applying NiCo-NPs as catalyst in ACN medium, where 81.6% BnOH conversion and 99% selectivity to benzaldehyde (BnCHO) were obtained. All catalyst conducted to better conversions and high BnCHO selectivity in ACN medium compared to aqueous medium. These results were attributed to biphasic aqueous - ACN system.